Stress hormones reduce the efficacy of paclitaxel in triple negative breast cancer through induction of DNA damage - Reeder, A. (2015)
Background: The mechanisms by which stress hormones impact triple-negative breast cancer (TNBC) etiology and treatment are unclear. We have previously shown that stress hormones, cortisol, and catecholamines induce rapid DNA damage and impact DNA repair in NIH 3T3 fibroblasts. This study investigates whether stress hormones increase DNA damage in breast cancer cells and if this impacts drug efficacy. Methods: We first screened a panel of 39 breast cancer cell lines for expression of adrenergic and glucocorticoid receptors and examined if stress hormones induce DNA damage and alter cell cycle regulation in vitro. A TNBC xenograft model was used to assess the impact of restraint stress on tumour growth and chemosensitivity to paclitaxel. Results: We found that stress hormones induced DNA damage, phosphorylation of ATR, which was accompanied by an up-regulation of the G1 cell kinase inhibitor p21 and a cell cycle halt of TNBCs in the G1 phase. p21 knockdown abrogated G1 arrest by stress hormones. We also demonstrated that stress significantly decreased efficacy of paclitaxel. Conclusion: We describe a novel mechanism through which stress hormones can induce drug resistance to paclitaxel, which may have profound implications for treating drug resistance in patients with TNBC.